2020
DOI: 10.1177/0886260520905076
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Our View: Demographic, Behavioral, and Contextual Factors in College Sexual Victimization

Abstract: Despite efforts on some college campuses to address the issue of sexual victimization, the numbers have not changed much over the last four decades. The purpose of this study is to examine how demographic, contextual, and behavioral factors influence sexual victimization on college campuses. Using data from the Fall 2011 National College Health Assessment/American College Health Association survey, we examine three hypotheses: (1) contextual factors will have a greater effect on the likelihood of victimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…For example, using large samples of schools (e.g., 474–524 institutions), studies have found that schools with larger student body size (Moylan et al, 2019; Stotzer & MacCartney, 2016) and campuses that are primarily residential (Stotzer & MacCartney, 2016) have higher rates of sexual assault victimization. However, in an analysis of 44 institutions that included these factors along with personal demographic characteristics and behavioral factors (e.g., personal substance use), neither campus size nor residentiality were associated with sexual assault victimization after accounting for personal characteristics (Rogers & Rogers, 2020). Of note, the latter study (with only 44 campuses) may have been underpowered to detect the effects of institutional factors on sexual assault victimization rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, using large samples of schools (e.g., 474–524 institutions), studies have found that schools with larger student body size (Moylan et al, 2019; Stotzer & MacCartney, 2016) and campuses that are primarily residential (Stotzer & MacCartney, 2016) have higher rates of sexual assault victimization. However, in an analysis of 44 institutions that included these factors along with personal demographic characteristics and behavioral factors (e.g., personal substance use), neither campus size nor residentiality were associated with sexual assault victimization after accounting for personal characteristics (Rogers & Rogers, 2020). Of note, the latter study (with only 44 campuses) may have been underpowered to detect the effects of institutional factors on sexual assault victimization rates.…”
Section: Resultsmentioning
confidence: 99%
“…• Public versus private (Oriol et al, 2019;Robers et al, 2014) • Co-ed versus not (Mucherah et al, 2018) • Public versus private (Fernandez & Lizotte, 1995;Fox & Hellman, 1985;Sloan, 1992;Stotzer & Hossellman, 2012) (Bromley, 1994;Paschall et al, 2011;Van Dyke & Tester, 2014) • Public versus private (Damewood, 2019;Kaasa et al, 2016;Moylan et al, 2019;Oriol et al, 2019;Wiersma-Mosley et al, 2017) (Ford, 2017;Graham et al, 2019Graham et al, , 2020Mohler-Kuo et al, 2004;Paschall et al, 2011 (Fernandez & Lizotte, 1995;Fox & Hellman, 1985;Sloan, 1994;Stotzer & Hossellman, 2012) (McPheters, 1978…”
Section: Sexual Assaultmentioning
confidence: 99%
“…The present study found gender and sexual orientation to be the strongest predictors of SV protective factors amongst other demographics, and should be considered throughout program design. Women and queer students are more likely to be assaulted; therefore, they have a greater inclination to be receptive to gender-segregated program design (de Heer & Jones, 2017;Rogers & Rogers, 2020). Prior research has indicated gender-segregated training appears more effective (Anderson & Whiston, 2005;Berkowitz, 2002;Jackson & Davis, 2000), as men can become more defensive on topics of SV in the presence of women (Brecklin & Forde, 2001;Rozee & Koss, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Gender and sexual orientation demographic variables had the greatest effect on all outcomes and are considered salient identities in the context of SV prevention education (de Heer & Jones, 2017; Rogers & Rogers, 2020). Prior studies on gender and sexual minorities demonstrated certain populations of queer students, gay men, bisexual women, and especially transgender people are at an increased risk of SV on college campuses (Cantor et al, 2020;Johnson et al, 2016) and, therefore, may be more sensitive to social norms regarding SV.…”
Section: Student-level Predictors Of Sexual Violence Protective Factorsmentioning
confidence: 99%
See 1 more Smart Citation